Implikasi Yuridis Peraturan Mahkamah Agung Nomor 13 Tahun 2016 dalam Putusan Hakim - Haniah, Haniah (University of Merdeka Malang, 2018)
Criminal liability with corporation subject hasn’t regulated in Criminal Code and Criminal Code Procedures in Indonesia, but the law outside Criminal Code Procedures has already admitted that corporation is a law subject. The Supreme Court Law Number 13 in 2016 about Procedures for the Submission of Handling Case of a Criminal Act by Corporate became the new rule as the reference for criminal code procedures as corporate law subject because there was no law rule about how to make an indictment, a prosecution letter, and others in this Supreme Court Law. With this Supreme Court Law, it is expected that the law enforcement can ensnare more corporations who do criminal acts. In this study, the writer is will discuss how the criminal liability of corporation works before and after the Supreme Court Law Number 13 in 2016 about Procedures for the Submission of Handling Case of a Criminal Act by Corporate in three verdicts. This study will reveal whether Supreme Court Law Number 13 in 2016 about Procedures for the Submission of Handling Case of a Criminal Act by Corporate can be a good and correct guidance of how law runs in criminal code with a law corporation as the subject.DOI: https://doi.org/10.26905/idjch.v9i2.2731